Connectivity Emotional Brand, Brand Love, Bridging Transition Process from Satisfaction to Loyalty (Evidenced from Samsung) - John Tampil Purba; Sylvia Samuel; Diego; Hardi Basoeki; Song Yup Lee (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to analyze the positive effects of brand satisfaction, brand love, and emotional brand attachment on brand loyalty and customer loyalty. The research was conducted over four months, from August to November 2021, using a quantitative approach through online questionnaires distributed via Google Forms. A total of 300 respondents participated in this study. Data analysis was performed using SPSS and SEM AMOS software. The results indicate that all six proposed hypotheses are statistically significant. Brand satisfaction, brand love, and emotional brand attachment positively influence brand loyalty. Furthermore, brand satisfaction, brand loyalty, and emotional brand attachment also have a positive impact on customer loyalty. These findings highlight the importance of emotional and experiential factors in building long-term relationships between brands and consumers.